Inorganic soil amendments alter seedling performance of native plant species in post-mining arid zone rehabilitation - Bateman, Amber M.; Erickson, Todd E.; Merritt, David J.; Muñoz-Rojas, Miriam (Journal of environmental management, 2019)
Rehabilitation of degraded drylands is challenged by environmental and anthropogenic constraints, such as limited availability of locally-sourced topsoil and poor quality alternative soil substrates. Current rehabilitation practices, at times, utilise inorganic soil amendments to improve the physicochemical and biological characteristics of reconstructed soil profiles. These approaches may be appropriate for dryland rehabilitation, but there is limited research available regarding the benefits of using these amendments. Here, we present a study in the Pilbara region of Western Australia, an arid landscape subject to intensive mining that currently uses inorganic soil amendments (gypsum and urea) in post-mining rehabilitation. The aim of this study was to assess the effectiveness of these amendments to (1) promote seed germination, seedling emergence and seedling growth across five plant species and, (2) re-instate soil quality in mine waste substrates. A series of glasshouse experiments assessed eight application combinations of these amendments in two alternative substrates and compared these to unamended substrates and topsoil. Soil amendments had a limited influence on seed germination, were detrimental to seedling emergence and resulted in increased seedling mortality. Mortality in the waste ranged from 2 to 61% but increased to 7–92% in amended waste. Seedling growth improved with high doses of amendments in waste, with a 1.3–5.6-fold increase across all plant species. Soil quality was relatively unaffected by amendments with soil nitrogen ranging from 0.01 to 0.08%, organic carbon from 0.01 to 0.12% and soil microbial activity from 2.3 to 2.4 ppm-CO2 in the amended and unamended waste. The use of soil amendments in mine rehabilitation requires consideration of the trade-off between initial reductions in seedling recruitment and enhanced seedling development at later stages. Future rehabilitation should consider the timing of amendment application to avoid detrimental impacts on seedling recruitment and maximise the benefits to seedling growth. [Display omitted] •Inorganic amendments were added to mine soils to assess plant and soil responses.•The percentage of germination and emergence of plants was highest in topsoil.•Plant responses to amendments varied across species and through plant life cycles.•Soil responses were similar across all mine soil treatments.•This study helps understand how agriculture practices can benefit arid restoration.